ECONOMY MANAGEMENT REFORMULATION THROUGH CORPORATE MANAGEMENT APPLICATIONS - Maria, GĂF-DEAC (Strategii Manageriale)
The paper presents conceptual aspects of corporate management on the reformulation of the economy. The central aim of the reformulation process management Romanian and European economy is entering into economic science and practice of corporate logic, modal logic as part of trust and distrust, to operate the new network economy based on knowledge. It concludes that, in fact, the utmost importance of corporate social responsibility proves practical and effective in the management of the economy reformulation. It is said that success and key future performance of the Romanian economy is a model integrated eneralized corporate management, the project outlined in the article, regarding conceptual and practical regulatory alignments new modern enterprises corporate behavior.